Strengthening the Global Trade Architecture for Development - Hoekman, Bernard (World Bank, Washington, DC, 2013)
Despite recurring rounds of trade liberalization, under the auspices of the World Trade Organization (and its predecessor, the General Agreement on Tariffs and Trade, or GATT). Complemented by unilateral reforms, many developing countries have not been able to integrate into the world economy. The author argues that from the perspective of the poorest countries, a multi-pronged strategy is required to strengthen the global trading system. Moreover, much of the agenda must be addressed outside the WTO. The most important contribution the WTO can make to development, is to improve market access conditions - for goods and services - and ensure that trade rules are useful to developing countries. Enhancing trade capacity requires concerted action outside the WTO ("aid for trade") as well as unilateral actions by both industrial, and developing countries to reduce anti-trade biases.